Analysis of the data from the Hospital Infection Surveillance System of the State of São Paulo – 2009 - Brandão de Assis, Denise; Madalosso, Geraldine; Ferreira, Sílvia Alice; Y. Yassuda, Yara (BEPA. Boletim Epidemiológico Paulista, 2010)
Yearly issuing and discussion of hospital infection rates (IH) are ongoing activities of the Hospital Infection Surveillance System of the State of São Paulo since implanted, in 2004. Increase tendencies of the number of notifying hospitals, registered in previous years, has been maintained in 2009, revealing the consolidation of this system. Hospital infection rates obtained allow the planning of actions for prevention and control of IH in the State. Projects designed to evaluate the relationship between antibiotic use and microbial resistance and also designed to reduce infection indexes in the blood flow are under way.